Gain and pain: resilience of home mobility in early Shabiyat housing of Ras Al-Khaimah - Assi, Eman (Frontiers in Built Environment, 2023)
The Social Housing Program initiated by the United Arab Emirates Government in 1971 aimed to upgrade the living conditions of the local Emiratis. The early housing projects were later known as Shabiyat. Individuals living in harsh conditions in the mountains of Ras Al Khaimah were willingly and within a short period relocated to new houses an approximate distance from their original homes, and they had to adapt to the new lifestyle and place. Due to changes in these individuals’ everyday practices, they questioned the resilience of their new houses. This study aimed to investigate the degree of resilience of the early Shabiyat housing and examine the notion of home mobility and how it is related to resilience through physical and nonphysical spatial transformation and everyday practice. The study is structured into two sections: first, understanding the resilience of the traditional settlements in the mountains; and second, examining the main characteristics of early Shabiyat, its main concept, and how it has addressed the Emirati society’s needs. This will assist in tracing these structures’ patterns of resilience and offer some practical guidance for professionals and the public in developing policies toward maximizing the sustainability of proposed future social housing projects.